Injectable dura mater sealant with adjustable mechanical property as well as preparation method and application of injectable dura mater sealant
By developing an injectable dura sealant, the rapid reaction of polymer and modified nanocellulose is used to form a gel network, and the problems of long gel time and unstable mechanical properties of dura sealant in the prior art are solved, and the gel time of dura sealant is short, adjustable mechanical strength, strong adhesion, low toxicity, low swelling rate and antibacterial analgesic effects of dura sealant are achieved.
Patent Information
- Application Number
- CN202411777209.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The existing dura sealing technology has problems such as long gel time, unstable mechanical properties, insufficient adhesion, high swelling rate, high toxicity or foreign body reaction, and it is difficult to meet the high requirements for immediate water sealing during surgery.
Develop an injectable dura sealant to form a gel network through rapid reaction between polymer groups, use modified nanocellulose to regulate mechanical properties, add antibacterial agents and pain-relieving drugs to improve adhesion and functionality, and enhance adhesion through the reaction of polymers with tissue amino groups.
The dural sealant has achieved short gel time, adjustable mechanical strength, strong adhesion, low toxicity, low swelling rate and antibacterial analgesic effects, which significantly improves the water sealing and safety during surgery.
Smart Images

Figure CN119587742A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical adhesives, and in particular relates to an injectable dura mater sealant with adjustable mechanical properties, a preparation method and an application thereof. Background Art
[0002] In surgery, urgent and effective dural sealing closure is very important to prevent cerebrospinal fluid (CSF) leakage, because once CSF leakage occurs, the dura mater will not heal itself, and CSF will flow into the epidural space, leading to neurological death. In addition, persistent CSF leakage will also bring many complications, such as wound rupture, incisional infection, meningitis, and epidural abscess, thereby increasing patient morbidity and mortality. To date, there are many methods for dural repair, including suture, adhesive, hydrogel, and dural substitute. Direct suture is the classic and commonly used dural closure technique in surgery, but in theory, it is difficult to achieve watertight closure by simple direct suture, attributed to the inevitable tiny needle holes left by the suture needle; autologous, allogeneic or xenogeneic collagen connective tissue transplantation and synthetic connective tissue are often used in clinical practice, but they always have many potential risks, such as nerve compression, incomplete closure, and toxicity.
[0003] Although some biohydrogel products (cellulose glue, gelatin, collagen sponge, etc.) have also been used for dura mater closure, their shortcomings such as insufficient tissue adhesion, difficulty in forming gels in liquid environments, rapid degradation, excessive expansion ratio, and troublesome preparation limit their further development. As a typical representative of bioadhesives, Dura Seal Dura Seal System is a commercial synthetic polyethylene glycol (PEG) hydrogel sealant used for dura mater sealing during surgery, but it can only be used after primary repair suture.
[0004] CN117298324A discloses a medical glue obtained by cross-linking multi-arm polyethylene glycol succinimidyl succinate and multi-arm polyethylene glycol amine. The medical glue is used for dura mater repair, which can make up for the shortcomings of suture repair method, effectively reduce cerebrospinal fluid leakage, shorten operation time, and reduce the incidence of intracranial infection.
[0005] The above methods are all based on the primary suturing of the dura mater, which requires superb surgical skills and carries the risk of secondary injury. In addition, suturing may not be possible when the dura mater tear or defect occurs at the branch of the nerve root. Based on the prevalence of dura mater defects and the high requirement for immediate water tightness during surgery, sutureless dura mater repair appears promising because it can significantly shorten the operation time and reduce surgical risks.
[0006] Therefore, to solve the above problems, it is urgent to develop a sutureless dura mater sealant with the advantages of short gel time, easy operation, low swelling rate, high mechanical strength, strong and durable adhesion to the dura mater, appropriate biodegradability, low toxicity or low foreign body reaction. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide an injectable dura mater sealant with adjustable mechanical strength, and a preparation method and application thereof. The dura mater sealant provided by the present invention has the advantages of short gel time, adjustable mechanical strength, high adhesion, high safety, simple operation, low swelling rate, etc., and has a certain antibacterial and analgesic effect, and can better prevent CSF leakage.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a dura mater sealant, characterized in that it comprises the following components by mass percentage:
[0010]
[0011] The dura mater sealant provided by the present invention comprises a polymer, modified nanocellulose, an antibacterial agent, an analgesic drug and a color marker in a specific mass ratio, utilizes the rapid reaction between polymer groups to form a gel network, and controls the mechanical properties of the prepared dura mater sealant by controlling the amount of modified nanocellulose added; relying on the reaction between the polymer and the amino groups in the tissue, the prepared dura mater sealant can be instantly adhered to the tissue surface and has strong adhesion; further, the present invention adds an antibacterial agent and analgesic drug to the sealant, thereby enhancing the functionality of the dura mater sealant; and a dura mater sealant with short gel time, adjustable mechanical strength, strong tissue adhesion, low toxicity, low swelling rate and certain antibacterial and analgesic effects is obtained.
[0012] Wherein, the polymer can be 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94% or 95%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0013] Wherein, the modified nanocellulose can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0014] Among them, the antibacterial agent can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0015] Among them, the antibacterial agent can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0016] Wherein, the color marker can be 0.01%, 0.015%, 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045% or 0.05%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0017] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0018] Preferably, the polymer is selected from at least two of four-arm polyethylene glycol succinimidyl glutarate, four-arm polyethylene glycol succinimidyl succinate, amino-terminated four-arm polyethylene glycol, four-arm polyethylene glycol epoxy, six-arm polyethylene glycol succinimidyl glutarate, six-arm polyethylene glycol succinimidyl succinate, amino-terminated six-arm polyethylene glycol, six-arm polyethylene glycol epoxy, eight-arm polyethylene glycol succinimidyl glutarate, eight-arm polyethylene glycol succinimidyl succinate, amino-terminated eight-arm polyethylene glycol, eight-arm polyethylene glycol epoxy, poly-ε-lysine, polyethyleneimine, chitosan or polydopamine.
[0019] Preferably, the polymer comprises polymer A and polymer B.
[0020] Preferably, polymer A is selected from at least one of four-arm polyethylene glycol succinimidyl glutarate, four-arm polyethylene glycol succinimidyl succinate, amino-terminated four-arm polyethylene glycol, four-arm polyethylene glycol epoxy, six-arm polyethylene glycol succinimidyl glutarate, six-arm polyethylene glycol succinimidyl succinate, amino-terminated six-arm polyethylene glycol, six-arm polyethylene glycol epoxy, eight-arm polyethylene glycol succinimidyl glutarate, eight-arm polyethylene glycol succinimidyl succinate, amino-terminated eight-arm polyethylene glycol, and eight-arm polyethylene glycol epoxy;
[0021] Preferably, polymer B is selected from at least one of poly-ε-lysine, polyethyleneimine, chitosan or polydopamine.
[0022] Preferably, the modified nanocellulose is amino-modified nanocellulose.
[0023] The modified nanocellulose forms hydrogen bonds in the gel network by cross-linking with the polymer, which can enhance the mechanical properties of the sealant. Further, the present invention controls the mechanical properties of the prepared dura sealant by controlling the amount of modified nanocellulose added, so that the prepared dura sealant has adjustable and relatively high mechanical strength.
[0024] Preferably, the antibacterial agent is one or more of vancomycin, cefepime, ceftazidime and meropenem.
[0025] Preferably, the analgesic drug is one or more of ibuprofen, acetaminophen, and acetylsalicylic acid.
[0026] Preferably, the color marker is one or more of brilliant blue pigment, lemon yellow, and gardenia blue pigment.
[0027] The raw materials used in the present invention are all non-toxic or low-toxic, so the dura mater sealant has the advantage of high safety.
[0028] Preferably, the method for preparing the amino-modified nanocellulose comprises the following steps:
[0029] (1) preparing epoxidized nanocellulose;
[0030] (2) Aminated nanocellulose is prepared by reacting epoxidized nanocellulose with ammonia water.
[0031] Preferably, the method for preparing epoxidized nanocellulose comprises the following steps:
[0032] (1a) alkalizing and bleaching the ascidian powder to obtain purified ascidian powder;
[0033] (1b) hydrolyzing the purified ascidian powder obtained in step (1a) with an acidic solution to obtain a nanocellulose suspension;
[0034] (1c) reacting the nanocellulose suspension obtained in step (1b) with epichlorohydrin to obtain epoxidized nanocellulose.
[0035] Preferably, the alkalization treatment method in step (1a) specifically comprises: mixing the ascidian powder and an alkaline aqueous solution to complete the alkalization treatment.
[0036] Preferably, the alkaline solution is a NaOH solution.
[0037] Preferably, the weight percentage concentration of the NaOH solution is 4-6wt%, for example, 4wt%, 4.5wt%, 5wt%, 5.5wt% or 6wt%.
[0038] Preferably, the mixing is performed at 70-90° C., such as 70° C., 75° C., 80° C., 85° C. or 90° C. Preferably, the mixing time is 12-18 h, such as 12 h, 13 h, 14 h, 15 h, 16 h, 17 h or 18 h.
[0039] Preferably, the bleaching method in step (1a) specifically comprises: mixing the alkaline treated ascidian powder with a bleaching agent to complete the mixing treatment.
[0040] Preferably, the bleaching agent is one of hydrogen peroxide, chlorine water or a mixture of acetic acid and sodium hypochlorite, and more preferably a mixture of acetic acid and sodium hypochlorite.
[0041] Preferably, the weight percentage concentration of acetic acid in the mixed solution is 1.0-1.5wt%, for example, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%.
[0042] Preferably, the weight percentage concentration of sodium hypochlorite in the mixed solution is 1.5-2.0wt%, for example, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt% or 2.0wt%.
[0043] Preferably, the alkalization treatment in step (1a) further includes washing and drying steps.
[0044] Preferably, the hydrolysis treatment method in step (1b) specifically comprises: mixing the purified ascidian powder and the acidic solution to complete the hydrolysis treatment.
[0045] Preferably, the acidic solution in step (1b) is an aqueous sulfuric acid solution.
[0046] Preferably, the weight percentage concentration of sulfuric acid in the aqueous sulfuric acid solution is 60-70wt%, for example, 60wt%, 62wt%, 64wt%, 66wt%, 68wt% or 70wt%, more preferably 64wt%.
[0047] Preferably, the hydrolysis treatment time in step (1b) is 2 to 4 h, for example, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h or 4 h.
[0048] Preferably, the temperature of the hydrolysis treatment in step (1b) is 45-55°C, for example, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C or 55°C.
[0049] Preferably, the hydrolysis treatment in step (1b) further includes washing and dialysis steps.
[0050] Preferably, the dialysis time is 48 to 96 h, for example 48 h, 52 h, 56 h, 60 h, 64 h, 68 h, 72 h, 76 h, 80 h, 84 h, 88 h, 92 h or 96 h.
[0051] Preferably, the step (1c) further comprises concentrating and alkalizing the nanocellulose suspension before the reaction.
[0052] Preferably, the concentration treatment is to concentrate the nanocellulose suspension until the mass fraction of nanocellulose in the nanocellulose suspension is 0.8-1.2wt%, for example 0.8wt%, 0.85wt%, 0.9wt%, 0.95wt%, 1.0wt%, 1.05wt%, 1.1wt%, 1.15wt% or 1.2wt%.
[0053] Preferably, the alkalization treatment method specifically comprises: mixing the concentrated nanocellulose suspension and an alkaline solution to complete the alkalization treatment.
[0054] Preferably, the alkaline solution used in the alkalization treatment is a NaOH solution.
[0055] Preferably, the weight percentage concentration of the NaOH solution is 1.5-2wt%, for example, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2wt%.
[0056] Preferably, the alkalization treatment is to adjust the system to pH=11-13, for example, pH=11, pH=11.2, pH=11.4, pH=11.6, pH=11.8, pH=12.0, pH=12.2, pH=1.24, pH=12.6, pH=12.8 or pH=13;
[0057] Preferably, the mass ratio of nanocellulose to epichlorohydrin in the nanocellulose suspension of step (1c) is 1:(0.8-1.2), for example, 1:0.8, 1:0.9, 1:1, 1:1.1 or 1:1.2.
[0058] Preferably, the reaction time of step (1c) is 1 to 4 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h.
[0059] Preferably, the reaction temperature in step (1c) is 60-70°C, for example 60°C, 61°C, 62°C, 63°C 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C.
[0060] Preferably, the reaction in step (1c) further includes washing and dialysis steps.
[0061] Preferably, the dialysis time is 48 to 96 h, for example 48 h, 52 h, 56 h, 60 h, 64 h, 68 h, 72 h, 76 h, 80 h, 84 h, 88 h, 92 h or 96 h.
[0062] Preferably, step (2) further includes alkalization treatment before the reaction.
[0063] Preferably, the alkalization treatment method specifically comprises: mixing the epoxidized nanocellulose and an alkaline solution to complete the alkalization treatment.
[0064] Preferably, the alkaline solution used is NaOH solution.
[0065] Preferably, the weight percentage concentration of the NaOH solution is 1.5-2wt%, for example, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2wt%.
[0066] Preferably, the alkalization treatment is to adjust the system to pH=11-13, for example, pH=11, pH=11.2, pH=11.4, pH=11.6, pH=11.8, pH=12.0, pH=12.2, pH=1.24, pH=12.6, pH=12.8 or pH=13.
[0067] Preferably, the ratio of the aqueous ammonia to the epoxidized nanocellulose in step (2) is 5 to 8 mL / g, for example, 5 mL / g, 5.5 mL / g, 6 mL / g, 6.5 mL / g, 7 mL / g, 7.5 mL / g or 8 mL / g.
[0068] Preferably, the reaction temperature in step (2) is 60-65°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C.
[0069] Preferably, the reaction time of step (2) is 1 to 3 h, for example, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2.0 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h.
[0070] Preferably, the reaction in step (2) further includes washing and dialysis steps.
[0071] Preferably, the dialysis time is 48 to 96 h, for example 48 h, 52 h, 56 h, 60 h, 64 h, 68 h, 72 h, 76 h, 80 h, 84 h, 88 h, 92 h or 96 h.
[0072] As a preferred technical solution of the present invention, the preparation method of the amino nanocellulose specifically comprises the following steps:
[0073] A 4-6 wt% NaOH solution is mixed with natural sea squirt powder at 70-90°C for 12-18 hours, and the obtained product is washed with deionized water until neutral and then placed in an oven for drying. Then, a bleaching agent containing 1.0-1.5 wt% acetic acid and 1.5-2.0 wt% sodium hypochlorite is added to bleach the sea squirt powder after alkalization treatment, and the obtained product after bleaching treatment is washed with deionized water until neutral and then placed in an oven for drying to obtain purified sea squirt powder.
[0074] The purified ascidian powder is hydrolyzed with a 60-70wt% sulfuric acid aqueous solution at 45-55°C for 2-4h to obtain a nanocellulose suspension, the obtained nanocellulose suspension is centrifuged and washed with deionized water, and then dialyzed in deionized water for 48-96h to obtain a uniformly dispersed nanocellulose suspension.
[0075] The obtained uniformly dispersed nanocellulose suspension is concentrated to a mass fraction of nanocellulose in the nanocellulose suspension of 0.8-1.2wt%, the system is adjusted to pH=11-13 with a 1.5-2wt% NaOH solution, epichlorohydrin is added, the mass ratio of nanocellulose to epichlorohydrin in the nanocellulose suspension is 1:(0.8-1:1.2), the reaction is carried out at 60-70°C for 1-4h, after the reaction is completed, the nanocellulose is washed by centrifugation with deionized water, and then dialyzed in deionized water for 48-96h to obtain epoxidized nanocellulose.
[0076] The obtained epoxidized nanocellulose is adjusted to pH 11-13 with 1.5-2wt% NaOH solution, and ammonia water is added, the ratio of ammonia water to epoxidized nanocellulose is 5-8mL / g, and the reaction is carried out at 60-65°C for 1-3h. After the reaction is completed, it is centrifuged and washed with deionized water, and then dialyzed in deionized water for 48-96h to obtain amino nanocellulose.
[0077] In a second aspect, the present invention provides a method for preparing the dura mater sealant according to the first aspect, comprising the following steps:
[0078] (S1) dispersing the modified nanocellulose in water, adding polymer A, optionally an antibacterial agent and optionally an analgesic, stirring, and reacting to obtain a suspension A;
[0079] (S2) dissolving polymer B in a buffer solution, adding an optional color marker to dissolve the solution, and obtaining solution B for later use;
[0080] (S3) The suspension A is mixed with the solution B to obtain the dura mater sealant.
[0081] Preferably, the amount of polymer A added in step (S1) and the amount of polymer B added in step (S2) are the same.
[0082] Preferably, the reaction conditions in step (S1) are 15-35°C, for example, 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C.
[0083] Preferably, the buffer solution in step (S1) is sterile water.
[0084] Preferably, the stirring speed in step S1 is 30-50 rpm, for example, 30 rpm, 31 rpm, 32 rpm, 33 rpm, 34 rpm, 35 rpm, 36 rpm, 37 rpm, 38 rpm, 39 rpm, 40 rpm, 41 rpm, 42 rpm, 43 rpm, 44 rpm, 45 rpm, 46 rpm, 47 rpm, 48 rpm, 49 rpm or 50 rpm.
[0085] Preferably, the reaction time in step (S1) is 1 to 3 h, for example, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2.0 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h.
[0086] Preferably, after the polymer and color marker are dissolved in step S2, they are stored at -20 to -18°C, for example, -18°C, -18.1°C, -18.2°C, -18.3°C, -18.4°C, -18.5°C, -18.6°C, -18.7°C, -18.8°C, -18.9°C, -19°C, -19.1°C, -19.2°C, -19.3°C, -19.4°C, -19.5°C, -19.6°C, -19.7°C, -19.8°C, -19.9°C or -20°C.
[0087] Preferably, the mixing in step S3 is performed by using a double-barrel syringe, and the suspension A and the solution B are added into two barrels of the double-barrel syringe respectively, and the mixture is evenly mixed in a mixing head and then extruded into a gel.
[0088] In a third aspect, the present invention provides a use of the dura mater sealant according to the third aspect in preparing a seamless dura mater sealant and a sealing material.
[0089] The beneficial effects of the present invention are:
[0090] (1) The present invention utilizes the reaction between polymer A and polymer B and modified nanocellulose to quickly cross-link to form a gel structure, and then adds an appropriate amount of antibacterial agent, analgesic drug and color marker. The obtained dura mater sealant has the advantages of short gel time, adjustable mechanical strength, strong tissue adhesion, low toxicity, low swelling rate, and antibacterial and analgesic properties.
[0091] (2) The present invention enhances the adhesion between the dura mater sealant and tissue through the reaction between the added polymer and tissue protein, and has strong adhesion performance even in an environment with water.
[0092] (3) The present invention diversifies the functions of the dura mater sealant by adding antibacterial agents and analgesics, and can be used in a variety of environments.
[0093] (4) The present invention utilizes the hydrolysis ability of the polymer in the in vivo water environment to achieve the regulation of its swelling behavior. Although the prepared dura sealant has a high swelling rate in vitro, the swelling rate of the dura sealant in vivo is low due to the certain hydrolysis of the polymer in water in the in vivo environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0094] Figure 1 1 is the compressive stress-strain curve of the dura mater sealant of Examples 1 to 5.
[0095] Figure 2 This is the swelling rate curve of the dura mater sealant of Examples 1 to 5 in PBS buffer solution. DETAILED DESCRIPTION
[0096] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0097] The sources of raw materials used in the following examples and comparative examples are as follows:
[0098] 1. Bisamino-terminated four-arm polyethylene glycol A595539, from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0099] 2. Four-arm polyethylene glycol succinimidyl glutarate A478099, from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0100] 3. Four-arm polyethylene glycol succinimidyl succinate A595089, from Hai Aladdin Biochemical Technology Co., Ltd.;
[0101] 4. Poly-ε-lysine P303210, from Sinopharm Group;
[0102] 5. Polyethylenimine E107079, from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0103] 6. Polydopamine A303863, from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0104] 7. Chitosan C105799, from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0105] 8. Vancomycin, from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0106] 9. Cefepime, from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0107] 10. Ibuprofen, from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0108] 11. Acetylsalicylic acid, from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0109] 12. Acetaminophen, from Sinopharm Group;
[0110] 13. Ceftazidime, from Sinopharm Group;
[0111] 14. Brilliant blue pigment, from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0112] 15. Gardenia blue pigment, from Xi'an Rongzhen Biotechnology Co., Ltd.;
[0113] 16. Lemon yellow, from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0114] Example 1
[0115] An injectable dura mater sealant with adjustable mechanical properties, comprising, by mass percentage:
[0116]
[0117] Among them, polymer A is diamino-terminated four-arm polyethylene glycol (2.34 g) and four-arm polyethylene glycol succinimidyl glutarate (2.34 g), and polymer B is poly-ε-lysine (4.69 g).
[0118] The preparation method of the amino nanocellulose comprises the following steps:
[0119] 5wt% NaOH solution (1mmol) was mixed with natural sea squirt powder (8g) at 80°C for 15h, and the obtained product was washed with deionized water until neutral and then dried in an oven. Then 1.0wt% acetic acid (15mL) and 2.0wt% sodium hypochlorite solution (30mL) were added to bleach the sea squirt powder after alkali treatment, and the obtained product was washed with deionized water until neutral and then dried in an oven after bleaching.
[0120] The treated ascidian powder was hydrolyzed with 64 wt % aqueous sulfuric acid solution (202 mL) at 45° C. for 3 h to obtain a suspension, which was washed by centrifugation with deionized water and then dialyzed in deionized water for 72 h to obtain a uniformly dispersed nanocellulose suspension.
[0121] The nanocellulose suspension was concentrated to a mass fraction of 0.8 wt%, and the system pH was adjusted to 11 using 1.5 wt% NaOH (1 mmol) solution. Epichlorohydrin (0.8 g) was added and reacted at 60°C for 3 h. After the reaction, the suspension was centrifuged and washed, and dialyzed for 48 h to obtain epoxidized nanocellulose.
[0122] The obtained epoxidized nanocellulose was adjusted to a system pH of 11 using a 1.5 wt % NaOH (1 mmol) solution, and aqueous ammonia (6 mL) was added to react at 60° C. for 3 h. After the reaction was completed, the mixture was centrifuged and washed, and dialyzed for 48 h to obtain the aminated nanocellulose.
[0123] The preparation method of the dura sealant is as follows:
[0124] Aminated nanocellulose (0.5 g) was dispersed in water (50 mL), and diamino-terminated four-arm polyethylene glycol (2.34 g), four-arm polyethylene glycol succinimidyl glutarate (2.34 g), vancomycin (0.1 g) and ibuprofen (20 mg) were added, stirred at 30 rpm, and reacted at 15 ° C for 2 h to obtain suspension A;
[0125] Poly-ε-lysine (4.69 g) was placed in a 50 mL beaker, deionized water was added to dissolve it, and brilliant blue pigment (10 mg) was added, mixed evenly to obtain solution B, and placed in a -18 °C refrigerator for later use;
[0126] The suspension A and solution B are added into the two barrels of the double barrel syringe respectively, mixed evenly in the mixing head and then squeezed out to obtain the finished dura sealant.
[0127] Example 2
[0128] An injectable dura mater sealant with adjustable mechanical properties, the preparation method is the same as that of Example 1, except that the raw materials used, calculated by mass percentage, include:
[0129]
[0130]
[0131] Wherein, polymer A is four-arm polyethylene glycol succinimidyl glutarate (4.54 g); polymer B is poly-ε-lysine (1.51 g), chitosan (1.51 g), and polyethyleneimine (1.51 g).
[0132] The preparation method of the amino nanocellulose comprises the following steps:
[0133] 6wt% NaOH solution (1mmol) and natural sea squirt powder (10g) were mixed at 70°C for 12h, and the obtained product was washed with deionized water until neutral and then dried in an oven. Then 1.5wt% acetic acid (15mL) and 1.5wt% sodium hypochlorite solution (30mL) were added to bleach the sea squirt powder after alkali treatment. After bleaching, the obtained product was washed with deionized water until neutral and then dried in an oven.
[0134] The treated ascidian powder was hydrolyzed with 64 wt % aqueous sulfuric acid solution (202 mL) at 55° C. for 2.5 h to obtain a suspension, which was washed by centrifugation with deionized water and then dialyzed in deionized water for 84 h to obtain a uniformly dispersed nanocellulose suspension.
[0135] The nanocellulose suspension was concentrated to a mass fraction of 1.2 wt%, and the system pH was adjusted to 13 using 2 wt% NaOH (1 mmol) solution. Epichlorohydrin (1 g) was added and reacted at 65°C for 1 h. After the reaction, the suspension was centrifuged and washed, and dialyzed for 84 h to obtain epoxidized nanocellulose.
[0136] The obtained epoxidized nanocellulose was adjusted to a system pH of 13 using a 2 wt % NaOH (1 mmol) solution, and aqueous ammonia (6 mL) was added to react at 65° C. for 1 h. After the reaction was completed, the mixture was centrifuged and washed, and dialyzed for 84 h to obtain amino-modified nanocellulose.
[0137] The preparation method of the dura sealant is as follows:
[0138] Aminated nanocellulose (0.8 g) was dispersed in water (80 mL), and four-arm polyethylene glycol succinimidyl glutarate (4.54 g), ceftazidime (0.1 g) and ibuprofen (20 mg) were added, stirred at 40 rpm, and reacted at 25° C. for 1.8 h to obtain suspension A;
[0139] Poly-ε-lysine (1.51 g), chitosan (1.51 g) and polyethyleneimine (1.51 g) were placed in a 50 mL beaker, deionized water was added to dissolve, and gardenia blue pigment (10 mg) was added, mixed evenly to obtain solution B, and placed in a -20 °C refrigerator for later use;
[0140] The suspension A and solution B are added into the two barrels of the double barrel syringe respectively, mixed evenly in the mixing head and then squeezed out to obtain the finished dura sealant.
[0141] Example 3
[0142] An injectable dura mater sealant with adjustable mechanical properties, the preparation method is the same as that of Example 1, except that the raw materials used, calculated by mass percentage, include:
[0143]
[0144] The polymer A is diamino-terminated four-arm polyethylene glycol (2.1 g) and four-arm polyethylene glycol succinimidyl succinate (2.1 g); and the polymer B is chitosan (4.19 g).
[0145] The preparation method of the amino nanocellulose comprises the following steps:
[0146] 4wt% NaOH solution (1mmol) and natural sea squirt powder (12g) were mixed at 70°C for 18h, and the obtained product was washed with deionized water until neutral and then dried in an oven. Then 1.2wt% acetic acid (15mL) and 1.8wt% sodium hypochlorite solution (30mL) were added to bleach the sea squirt powder after alkali treatment, and the obtained product was washed with deionized water until neutral and then dried in an oven after bleaching.
[0147] The treated ascidian powder was hydrolyzed with 64 wt % aqueous sulfuric acid solution (202 mL) at 50° C. for 2.7 h to obtain a suspension, which was washed by centrifugation with deionized water and then dialyzed in deionized water for 72 h to obtain a uniformly dispersed nanocellulose crystal suspension.
[0148] The nanocellulose suspension was concentrated to a mass fraction of 1.2 wt%, and the system pH was adjusted to 12 using 1.7 wt% NaOH (1 mmol) solution. Epichlorohydrin (1.2 g) was added and reacted at 60°C for 2 h. After the reaction, the suspension was centrifuged and washed, and dialyzed for 72 h to obtain epoxidized nanocellulose.
[0149] The obtained epoxidized nanocellulose was adjusted to a system pH of 12 using a 1.7 wt% NaOH (1 mmol) solution, and aqueous ammonia (8 mL) was added to react at 60°C for 2 h. After the reaction, the mixture was centrifuged and washed, and dialyzed for 72 h to obtain the amino nanocellulose.
[0150] The preparation method of the dura sealant is as follows:
[0151] Aminated nanocellulose (1.5 g) was dispersed in water (150 mL), and diamino-terminated four-arm polyethylene glycol (2.1 g) and four-arm polyethylene glycol succinimidyl succinate (2.1 g), cefepime (0.1 g) and acetylsalicylic acid (20 mg) were added, and the mixture was stirred at 50 rpm and reacted at 35 °C for 2 h to obtain suspension A;
[0152] Chitosan (4.19 g) was placed in a 50 mL beaker, deionized water was added to dissolve, and brilliant blue pigment (10 mg) was added, mixed evenly to obtain solution B, and placed in a -20 °C refrigerator for later use;
[0153] The suspension A and solution B are added into the two barrels of the double barrel syringe respectively, mixed evenly in the mixing head and then squeezed out to obtain the finished dura sealant.
[0154] Example 4
[0155] An injectable dura mater sealant with adjustable mechanical properties, the preparation method is the same as that of Example 1, except that the raw materials used, calculated by mass percentage, include:
[0156]
[0157]
[0158] Wherein polymer A is four-arm polyethylene glycol succinimidyl glutarate (2.37 g) and four-arm polyethylene glycol succinimidyl succinate (2.37 g); polymer B is poly-ε-lysine (2.37 g) and polydopamine (2.37 g).
[0159] The amino nanocellulose used in Example 4 is the same as that in Example 1.
[0160] The preparation method of the dura sealant is as follows:
[0161] Aminated nanocellulose (0.1 g) was dispersed in water (10 mL), and four-arm polyethylene glycol succinimidyl glutarate (2.37 g), four-arm polyethylene glycol succinimidyl succinate (2.37 g), vancomycin (0.4 g) and acetaminophen (20 mg) were added, stirred at 40 rpm, and reacted at 25 ° C for 1.8 h to obtain suspension A;
[0162] Take poly-ε-lysine (2.37 g) and polydopamine (2.37 g) in a 50 mL beaker, add deionized water to dissolve, add tartrazine (10 mg), mix well to obtain solution B, and place in a -20 ° C refrigerator for later use;
[0163] The suspension A and solution B are added into the two barrels of the double barrel syringe respectively, mixed evenly in the mixing head and then squeezed out to obtain the finished dura sealant.
[0164] Example 5
[0165] An injectable dura mater sealant with adjustable mechanical properties, the preparation method is the same as that of Example 1, except that the raw materials used, calculated by mass percentage, include:
[0166]
[0167] Wherein polymer A is four-arm polyethylene glycol succinimidyl glutarate (19.6 g) and four-arm polyethylene glycol succinimidyl succinate (19.6 g); polymer B is chitosan (3.92 g).
[0168] The amino nanocellulose used in Example 5 is the same as that in Example 1.
[0169] The preparation method of the dura sealant is as follows:
[0170] Aminated nanocellulose (2 g) was dispersed in water (200 mL), and four-arm polyethylene glycol succinimidyl glutarate (2.22 g), four-arm polyethylene glycol succinimidyl succinate (2.22 g), vancomycin (0.1 g) and acetaminophen (50 mg) were added, and the mixture was stirred at 40 rpm and reacted at 25° C. for 2.4 h to obtain a suspension A;
[0171] Chitosan (4.44 g) was placed in a 50 mL beaker, deionized water was added to dissolve, and tartrazine (5 mg) was added, mixed evenly to obtain solution B, and placed in a -20 °C refrigerator for later use;
[0172] The suspension A and solution B are added into the two barrels of the double barrel syringe respectively, mixed evenly in the mixing head and then squeezed out to obtain the finished dura sealant.
[0173] Example 6
[0174] The difference from Example 1 is that polymer A is four-arm polyethylene glycol succinimidyl glutarate (4.68 g), and polymer B is poly-ε-lysine (4.69 g).
[0175] Example 7
[0176] The difference from Example 1 is that polymer A is diamino-terminated four-arm polyethylene glycol (4.68 g), and polymer B is poly-ε-lysine (4.69 g).
[0177] Comparative Example 1
[0178] The difference from Example 1 is that the amino-treated nanocellulose is replaced by epoxidized nanocellulose in an equal weight percentage.
[0179] Comparative Example 2
[0180] The difference from Example 1 is that the polymer is four-arm polyethylene glycol succinimidyl glutarate (9.37 g).
[0181] Performance Test:
[0182] Gel time: test method refers to GB 6783-1994;
[0183] Swelling rate: Test method refers to GB / T 16886.19;
[0184] Compression performance test: the test method refers to ASTM F1566-15;
[0185] Adhesion test: Test method refers to ASTM F2255-05;
[0186] Burst pressure test: the test method refers to ASTM F2392-04;
[0187] Table 1 Partial performance test results of dura mater sealants prepared in Examples 1 to 5
[0188]
[0189] It can be seen from Table 1 that the dura mater sealants prepared in Examples 1 to 7 of the present invention all have good mechanical properties, adhesion properties and strong anti-rupture ability. The rupture strength of all dura mater sealants is ≥270 mmH2O. Even when a person coughs or sneezes (CSF fluctuation pressure ≥250 mmH2O), rupture will not occur, and CSF leakage can be well blocked. In addition, the dura mater sealants prepared in each embodiment have an extremely short gelation time, which can ensure gelation during extrusion and meet the sealing requirements.
[0190] Among them, Example 3 has the highest compression strength, which is attributed to the large amount of modified nanocellulose added, which can form hydrogen bonds in the gel network and play the role of reinforcing filler, and the prepared dura sealant is harder; Example 4 has the largest adhesion strength, indicating that the addition of polydopamine improves its adhesion, which is more conducive to its application in the case of no suture after surgery, and because there are more residual succinimide groups, it promotes adhesion and has biocompatibility, further enhancing its adhesion strength.
[0191] Comparative Example 1 uses an equal mass percentage of epoxidized nanocellulose to replace the amino nanocellulose in Example 1. Compared with the amino nanocellulose, the epoxidized nanocellulose has a weaker ability to cross-link with the polymer, resulting in its ability to enhance the mechanical properties of the sealant being inferior to that of the amino nanocellulose.
[0192] Compared with Example 1, Comparative Example 2 only uses four-arm polyethylene glycol succinimidyl glutarate to replace the combination of diamino-terminated four-arm polyethylene glycol, four-arm polyethylene glycol succinimidyl glutarate and poly-ε-lysine in Example 1. According to the test results, it can be seen that the addition of only one polymer makes the gel performance and mechanical properties of the prepared dura mater sealant poor, and cannot meet the sealing requirements.
[0193] Figure 1 The compressive stress-strain curves of Examples 1 to 5 for different amounts of modified nanocellulose added are shown. As the amount of modified nanocellulose added increases, the strength and rupture pressure of the prepared dura sealants show an upward trend, indicating that the mechanical strength of the dura sealant is adjustable and the product can be reasonably selected according to different usage environments.
[0194] Figure 2 The swelling rate curves of Examples 1 to 5 are shown. It can be seen from the figure that since the raw materials are all hydrophilic substances, the swelling rate of the prepared dura sealant in PBS buffer solution (pH=7.4) is relatively high and changes with the formula. In the in vivo environment, due to the difference in water environment, the degradation effect on the prepared dura sealant is also different, so the maximum swelling rate of 98.74% appears on the first day, and thereafter due to the hydrolysis of four-arm polyethylene glycol, the swelling rate gradually decreases.
[0195] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A dura mater sealant, characterized in that: The dura mater sealant comprises the following components by mass percentage:
2. The dura mater sealant according to claim 1, characterized in that The polymer is selected from at least two of four-arm polyethylene glycol succinimidyl glutarate, four-arm polyethylene glycol succinimidyl succinate, amino-terminated four-arm polyethylene glycol, four-arm polyethylene glycol epoxy, six-arm polyethylene glycol succinimidyl glutarate, six-arm polyethylene glycol succinimidyl succinate, amino-terminated six-arm polyethylene glycol, six-arm polyethylene glycol epoxy, eight-arm polyethylene glycol succinimidyl glutarate, eight-arm polyethylene glycol succinimidyl succinate, amino-terminated eight-arm polyethylene glycol, eight-arm polyethylene glycol epoxy, poly-ε-lysine, polyethyleneimine, chitosan or polydopamine; Preferably, the polymer comprises polymer A and polymer B; Preferably, polymer A is selected from at least one of four-arm polyethylene glycol succinimidyl glutarate, four-arm polyethylene glycol succinimidyl succinate, amino-terminated four-arm polyethylene glycol, four-arm polyethylene glycol epoxy, six-arm polyethylene glycol succinimidyl glutarate, six-arm polyethylene glycol succinimidyl succinate, amino-terminated six-arm polyethylene glycol, six-arm polyethylene glycol epoxy, eight-arm polyethylene glycol succinimidyl glutarate, eight-arm polyethylene glycol succinimidyl succinate, amino-terminated eight-arm polyethylene glycol, and eight-arm polyethylene glycol epoxy; Preferably, polymer B is selected from at least one of poly-ε-lysine, polyethyleneimine, chitosan or polydopamine.
3. The dura mater sealant according to claim 1 or 2, characterized in that: The modified nanocellulose is amino-modified nanocellulose.
4. The dura mater sealant according to claims 1 to 3, characterized in that: The antibacterial agent includes one or a combination of at least two of vancomycin, cefepime, ceftazidime or meropenem; Preferably, the analgesic drug comprises one or a combination of at least two of ibuprofen, acetaminophen or acetylsalicylic acid; Preferably, the color marker comprises one or a combination of at least two of brilliant blue pigment, lemon yellow or gardenia blue pigment.
5. The dura mater sealant according to claims 1 to 4, characterized in that: The amino nanocellulose is prepared by the following method, which comprises the following steps: (1) preparing epoxidized nanocellulose; (2) Aminated nanocellulose is prepared by reacting epoxidized nanocellulose with ammonia water.
6. The dura mater sealant according to claims 1 to 5, characterized in that: The preparation method of the epoxidized nanocellulose comprises the following steps: (1a) alkalizing and bleaching the ascidian powder to obtain purified ascidian powder; (1b) hydrolyzing the purified ascidian powder obtained in step (1a) with an acidic solution to obtain a nanocellulose suspension; (1c) reacting the nanocellulose suspension obtained in step (1b) with epichlorohydrin to obtain epoxidized nanocellulose; Preferably, the alkalization treatment method in step (1a) specifically comprises: mixing the ascidian powder and the alkaline aqueous solution to complete the alkalization treatment; Preferably, the alkaline solution is a NaOH solution; Preferably, the weight percentage concentration of the NaOH solution is 4-6wt%; Preferably, the mixing is carried out at 70-90°C; Preferably, the mixing time is 12 to 18 hours; Preferably, the bleaching method in step (1a) specifically comprises: mixing the alkaline treated sea squirt powder with a bleaching agent to complete the mixing treatment; Preferably, the bleaching agent is one of hydrogen peroxide, chlorine water or a mixture of acetic acid and sodium hypochlorite, more preferably a mixture of acetic acid and sodium hypochlorite; Preferably, the weight percentage concentration of acetic acid in the mixed solution is 1.0-1.5wt%, and the weight percentage concentration of sodium hypochlorite is 1.5-2.0wt%; Preferably, the alkalization treatment in step (1a) further includes washing and drying steps; Preferably, the hydrolysis treatment method in step (1b) specifically comprises: mixing the purified ascidian powder and the acidic solution to complete the hydrolysis treatment; Preferably, the acidic solution in step (1b) is an aqueous solution of sulfuric acid; Preferably, the weight percentage concentration of sulfuric acid in the sulfuric acid aqueous solution is 60-70wt%, more preferably 64wt%; Preferably, the hydrolysis treatment time in step (1b) is 2 to 4 hours; Preferably, the temperature of the hydrolysis treatment in step (1b) is 45-55°C; Preferably, the hydrolysis treatment in step (1b) further includes washing and dialysis steps; Preferably, the dialysis time is 48 to 96 hours; Preferably, the step (1c) further comprises concentrating and alkalizing the nanocellulose suspension before the reaction; Preferably, the concentration treatment is to concentrate the nanocellulose suspension until the mass fraction of nanocellulose in the nanocellulose suspension is 0.8 to 1.2 wt %; Preferably, the alkalization treatment method specifically comprises: mixing the concentrated nanocellulose suspension and an alkaline solution to complete the alkalization treatment; Preferably, the alkaline solution used in the alkalization treatment is a NaOH solution; Preferably, the weight percentage concentration of the NaOH solution is 1.5-2wt%; Preferably, the alkalization treatment is to adjust the system to pH = 11-13; Preferably, the mass ratio of nanocellulose to epichlorohydrin in the nanocellulose suspension of step (1c) is 1:(0.8-1.2); Preferably, the reaction time in step (1c) is 1 to 4 hours; Preferably, the reaction temperature in step (1c) is 60-70°C; Preferably, the reaction in step (1c) further comprises washing and dialysis steps; Preferably, the dialysis time is 48 to 96 hours.
7. The dura mater sealant according to claims 1 to 6, characterized in that: The step (2) further comprises an alkalization treatment before the reaction; Preferably, the alkalization treatment method specifically comprises: mixing the epoxidized nanocellulose and an alkaline solution to complete the alkalization treatment; Preferably, the alkaline solution used is NaOH solution; Preferably, the weight percentage concentration of the NaOH solution is 1.5-2wt%; Preferably, the alkalization treatment is to adjust the system to pH = 11-13; Preferably, the ratio of ammonia water to epoxidized nanocellulose in step (2) is 5 to 8 mL / g; Preferably, the reaction temperature in step (2) is 60-65°C; Preferably, the reaction time in step (2) is 1 to 3 hours; Preferably, the reaction in step (2) further includes washing and dialysis steps; Preferably, the dialysis time is 48 to 96 hours.
8. A method for preparing the dura mater sealant according to any one of claims 1 to 7, characterized in that: The following steps are involved: (S1) dispersing the modified nanocellulose in water, adding polymer A, optionally an antibacterial agent and optionally an analgesic, stirring, and reacting to obtain a suspension A; (S2) dissolving polymer B in a buffer solution, adding an optional color marker to dissolve the solution, and obtaining solution B for later use; (S3) The suspension A is mixed with the solution B to obtain the dura mater sealant.
9. The method for preparing the dura mater sealant according to claim 8, characterized in that: The amount of polymer A added in step (S1) is the same as the amount of polymer B added in step (S2); Preferably, the reaction conditions in step (S1) are 15-35°C; Preferably, the buffer solution in step (S1) is sterile water; Preferably, the stirring speed in step (S1) is 30 to 50 rpm; Preferably, the reaction time in step (S1) is 1 to 3 hours; Preferably, the storage temperature of the solution B in step (S2) is -20 to -18°C; Preferably, the mixing in step (S3) is performed by using a double-barrel syringe, and the suspension A and the solution B are added into two barrels of the double-barrel syringe respectively, and the mixture is mixed evenly in a mixing head and then extruded into a gel.
10. Use of the dura mater sealant according to any one of claims 1 to 7 in the preparation of seamless dura mater sealant and sealing materials.
Citation Information
Patent Citations
Medical adhesive as well as preparation method and kit thereof
CN117298324A
Tissue sealant and preparation method and application thereof
CN105169469A
Aminated nano cellulose crystal and preparation method thereof
CN105646722A
Preparation method of amination nanometer cellulose whisker modified waterborne polyurethane
CN109880046A
Tissue-Adhesive Material
US20190307915A1